Safety, pharmacokinetics and target engagement of novel RIPK1 inhibitor SAR443060 (DNL747) for neurodegenerative disorders: Randomized, placebo‐controlled, double‐blind phase I/Ib studies in healthy subjects and patients - Maurits F. J. M. Vissers; Jules A. A. C. Heuberger; Geert Jan Groeneveld; Jerome Oude Nijhuis; Peter Paul De Deyn; Salah Hadi; Jeffrey Harris; Richard M. Tsai; Andres Cruz‐Herranz; Fen Huang; Vincent Tong; Rebecca Erickson; et al. (Wiley, 2022)
Abstract RIPK1 is a master regulator of inflammatory signaling and cell death and increased RIPK1 activity is observed in human diseases, including Alzheimer's disease (AD) and amyotrophic lateral sclerosis (ALS). RIPK1 inhibition has been shown to protect against cell death in a range of preclinical cellular and animal models of diseases. SAR443060 (previously DNL747) is a selective, orally bioavailable, central nervous system (CNS)-penetrant, small‐molecule, reversible inhibitor of RIPK1. In three early‐stage clinical trials in healthy subjects and patients with AD or ALS (NCT03757325 and NCT03757351), SAR443060 distributed into the cerebrospinal fluid (CSF) after oral administration and demonstrated robust peripheral target engagement as measured by a reduction in phosphorylation of RIPK1 at serine 166 (pRIPK1) in human peripheral blood mononuclear cells compared to baseline. RIPK1 inhibition was generally safe and well‐tolerated in healthy volunteers and patients with AD or ALS. Taken together, the distribution into the CSF after oral administration, the peripheral proof‐of‐mechanism, and the safety profile of RIPK1 inhibition to date, suggest that therapeutic modulation of RIPK1 in the CNS is possible, conferring potential therapeutic promise for AD and ALS, as well as other neurodegenerative conditions. However, SAR443060 development was discontinued due to long‐term nonclinical toxicology findings, although these nonclinical toxicology signals were not observed in the short duration dosing in any of the three early‐stage clinical trials. The dose‐limiting toxicities observed for SAR443060 preclinically have not been reported for other RIPK1‐inhibitors, suggesting that these toxicities are compound‐specific (related to SAR443060) rather than RIPK1 pathway‐specific.